GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PENYAKIT KANKER SERVIKS DI WILAYAH JAKARTA TIMUR - Suryani Hartati, Retno Winarti (Institut Kesehatan Hermina, 2020)
The cervical cancer mortality rate is still high, more than 92 thousand women in Indonesia among them due to cervical cancer, making it number two in the highest number in the world. this can be caused by the absence of an early monitoring process. Coverage of early cervical cancer coverage in Indonesia is very low, only around 5%. This is due to lack of knowledge about cervical cancer so that the incidence of cervical cancer increases every year. Objective: To describe mother’s knowledge level about cervical cancer in mothers age between 30 to 50 years in east Jakarta area. Method: This cross-sectional study applied a consecutive sampling technique to select 103 mothers in east Jakarta. This study had been conducted from june up August 2019. Data collected using questionnaire which consisted of mothers’ characteristic and mother’s knowledge level about cervical cancer. It has been tested for validity and reliability. The validity test using the Pearson product moment (r= 0,467-948), and reliability test with Cronbach Alpha (0.794). Result : the study showed that most of the mothers had low knowledge (75.7%). The results of the study proved that there is a relation between the level of education with knowledge about cervical cancer (p=0.000). Age, marital status, occupation, ethnicity have no relation with knowledge about cervical cancer Suggestions that researchers can give are nurses in providing counseling about cervical cancer to mothers, should look at the background level of mother's education so that mothers understand the knowledge received